2019
DOI: 10.1200/po.18.00326
|View full text |Cite
|
Sign up to set email alerts
|

Impact of KRAS and TP53 Co-Mutations on Outcomes After First-Line Systemic Therapy Among Patients With STK11-Mutated Advanced Non–Small-Cell Lung Cancer

Abstract: PURPOSE The STK11 gene encodes a serine/threonine protein kinase that regulates cell polarity and functions as a tumor suppressor. Patients with non-small-cell lung cancer (NSCLC) and STK11 mutations often have other co-mutations. We evaluated the impact of KRAS and TP53 co-mutations on outcomes after first-line systemic therapy for patients with metastatic or recurrent NSCLC that harbors STK11 mutations. METHODS We conducted a retrospective review of patients with metastatic NSCLC and STK11 mutations treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
2
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 26 publications
9
63
2
1
Order By: Relevance
“…patients with STK11m had a co-mutation in KRASm, which is largely consistent with the comutation frequencies reported previously [20,21,24,33].…”
Section: Plos Onesupporting
confidence: 91%
See 3 more Smart Citations
“…patients with STK11m had a co-mutation in KRASm, which is largely consistent with the comutation frequencies reported previously [20,21,24,33].…”
Section: Plos Onesupporting
confidence: 91%
“…The current data, in a large observational genomic study among patients receiving routine clinical care, support the association of STK11m with poor treatment outcomes previously observed in smaller clinical trial cohorts [18][19][20][21][22][23][24]. Shorter OS and reduced response rates have been observed in patients with STK11m versus STK11wt non-squamous metastatic NSCLC treated with durvalumab (with or without tremelimumab) across multiple phase 1/2 trials [18].…”
Section: Plos Onesupporting
confidence: 78%
See 2 more Smart Citations
“…Finally, another recent work showed that NSCLC patients with KRAS/STK11 co-mutation, treated with ICIs as second-or third-line of therapy, experienced a worse PFS and OS compared with those with STK11 mutation alone (median PFS, 2.4 months vs. 5.1 months, p = 0.048; median OS, 7.1 months vs. 16.1 months, p < 0.001) [159].…”
Section: Co-mutation Of Kras E Stk11mentioning
confidence: 96%